Ceratozetes (Ceratozetes) minutissimus Willmann 1951 - Murvanidze, Maka; Cilbircioğlu, Cihan; Özdemir, Esengül; Inak, Emre (Zenodo, 2020)
Published as part of Murvanidze, Maka, Cilbircioğlu, Cihan, Özdemir, Esengül & Inak, Emre, 2020, Checklist of oribatid mites (Acari: Oribatida) of the Central Black Sea basin of Turkey with new records for the country, pp. 255-277 in Persian Journal of Acarology 9 (3) on page 268, DOI: 10.22073/pja.v9i3.61909, http://zenodo.org/record/5236444

Ceratozetes (Ceratozetes) minutissimus Willmann, 1951 * Material – New record for Turkey. One specimen in Yeşiltepe forest area, Akçabat, Trabzon, N 40° 58′ 24.75′′, E 39° 30′ 25.55′′, alt. = 348 m, 22 May 2018, soil under P. sylvestris . Global distribution – Palaearctic. Ecology – Forest and meadow soils.
Keywords: Arthropoda; Ceratozetes minutissimus; Arachnida; Ceratozetidae; Animalia; Biodiversity; Sarcoptiformes; Ceratozetes; Taxonomy; 15. Life on land